Childhood Adversity and Intimate Partner Violence in Adulthood: The Mediating Influence of PTSD in a Sample of Women Prisoners. Issue 15 (August 2021) - Jones, Melissa S.; Peck, B. Mitchell; Sharp, Susan F.; McLeod, David A.
Although past research documents strong linkages between adverse childhood experiences (ACEs), posttraumatic stress disorder (PTSD), and adult intimate partner violence (IPV) in the lives of women prisoners, researchers have often neglected to consider the potential mediating role of PTSD in the relationships between ACEs and adult IPV. Using data from a stratified random sample of all incarcerated women in Oklahoma ( N = 334), we explore the relationships between ACEs, PTSD symptomology, and adult IPV utilizing a feminist life course theoretical framework. Results indicate that PTSD symptomology fully mediates the relationship between ACEs and adult IPV, suggesting that PTSD may be central to understanding pathways to adult IPV as well as offending and incarceration for women. Implications and suggestions for policy and future research are offered.